2018
DOI: 10.3389/fimmu.2018.03078
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Reason to Induce Acute Graft-vs.-Host Disease After Hematopoietic Stem Cell Transplantation: Lack of Sirtuin-1 in CD4+ T Cells

Abstract: Sirtuin 1 (SIRT1) is a critical suppressor of T cell immunity. However, whether SIRT1 is involved in the progression of acute graft-vs.-host disease (aGVHD) has still remained unclear. PI3K/Akt/mTOR pathway is a crucial element involved in the activation and functions of T cells. Over-activation of PI3K/Akt/mTOR signaling may be related to the occurrence of aGVHD. STAT3 activation requires phosphorylation and acetylation. A recent study showed that STAT3 hyperphosphorylation in CD4+ T cells may be a trigger of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Accumulating evidence suggests that the imbalance between Th17 cells and Tregs plays a critical role in aGVHD ( 17 19 , 37 39 ). Our previous research revealed that STAT3 overexpression and activation in CD4 + T cells from aGVHD cases is one of the causes of Th17/Treg imbalance ( 6 , 22 ). In this study, after CTCF overexpression in CD4 + T cells from aGVHD patients, p53, Foxp3, and IL-10 expression levels were significantly increased, while RORγt and IL-17A were significantly downregulated, thus reversing the Th17/Treg imbalance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence suggests that the imbalance between Th17 cells and Tregs plays a critical role in aGVHD ( 17 19 , 37 39 ). Our previous research revealed that STAT3 overexpression and activation in CD4 + T cells from aGVHD cases is one of the causes of Th17/Treg imbalance ( 6 , 22 ). In this study, after CTCF overexpression in CD4 + T cells from aGVHD patients, p53, Foxp3, and IL-10 expression levels were significantly increased, while RORγt and IL-17A were significantly downregulated, thus reversing the Th17/Treg imbalance.…”
Section: Discussionmentioning
confidence: 99%
“…The median time from transplantation to aGVHD onset was 53 (20–91) days. Conditioning regimens were adopted as described in our previous study ( 22 ). Assessment of aGVHD was based on clinical symptoms in accordance with reported criteria ( 23 , 24 ).…”
Section: Methodsmentioning
confidence: 99%
“…The clinical characteristics of the included patients are shown in Table 1 . Conditioning regimens were based on our previous study [ 57 ]. aGVHD was assessed based on clinical symptoms in accordance with commonly accepted criteria [ 58 , 59 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, conditional SIRT1 KO in T cells was further shown to induce Treg differentiation, thereby prolonging allograft survival 12 , 13 . However, a recent study on patients with acute graft-versus-host disease (aGVHD) revealed contradictory results, as SIRT1 deficiency in CD4 + T cells played a crucial role in upregulating STAT3 phosphorylation, in turn increasing Th17 differentiation and inducing aGVHD 14 . This latter finding was further supported by a study on SIRT1-deficient mice, in which T cells failed to maintain tolerance leading to the development of severe EAE 15 .…”
Section: Introductionmentioning
confidence: 99%